Shanaya: A new leafhopper genus of the tribe Mukariini (Cicadellidae: Deltocephalinae) with two new species discovered and described from India - Rajgopal, Nernakallu N.; Ramaiah, Mogili; Rai, Stuti; Dey, Debjani; Singaravel, Muniyandi; Meshram, Naresh M. (Zootaxa, 2025)
A new genus, Shanaya gen. nov., is proposed within the tribe Mukariini, based on the discovery of two new species from India that could not be assigned to any previously described genera. Detailed morphological descriptions and photographic illustrations are provided for both species: Shanaya spatulata gen. et sp. nov. (Type species, India: Himachal Pradesh) and Shanaya abeeri gen. et sp. nov. (India: Karnataka). Morphological evidence supports their classification under this new genus. A distribution map, along with identification keys to the genera of Mukariini of India and species of the new genus, are included. Its tribal placement, as well as similarities and differences with related genera, are also discussed. DNA barcodes (partial mitochondrial COI sequences) were generated for Shanaya spatulata gen. et sp. nov. and submitted to NCBI GenBank. All type specimens are housed in the National Pusa Collection (NPC), ICAR–Indian Agricultural Research Institute, New Delhi, University of Agricultural Sciences, Bengaluru (UASB) and National Insect Museum, ICAR–National Bureau of Agricultural Insect Resources, Bengaluru (NIM).